The Effectiveness of Learning Videos Using Canva Media on Elementary School Students' Motivation to Learn Science - Desak Made Darmawati; Nur Busyra; Trisni Handayani; M. Alimudin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Modernization of learning in industry 4.0, or the 21st century, is required to follow the development of science and technological progress, with the aim of being able to present a learning atmosphere that is enjoyable and in accordance with technological progress. This study aims to determine the effectiveness of learning videos using Canva media on the motivation to learn science in grade 5 students at Sabilina Kranggan Islamic Elementary School, Bekasi. the two variables between learning videos based on Canva media on students' learning motivation before being given a pre-test on the results of learning science, before treatment with Canva media-based video media showed the lowest obtained value of 50. Meanwhile, after using the Canva media-based video treatment on students' learning motivation after being given a post-test, the results of learning science can increase from an average value of 100. after being given treatment. This study was declared effective by proving the results of the student instrument with a sample size of 26 with a t-test greater than the t-table, namely -1.99 with -1.67, then Ho is rejected and Ha is accepted, meaning that there is an effectiveness of learning videos using Canva media on the motivation to learn science in grade 5 students at Sabilina Kranggan Islamic Elementary School, Bekasi Jatisampurna.